Diagnosis and Management of Heatstroke - I Gede Yasa Asmara (Acta Medica Indonesiana)
Heatstroke is a life-threatening  and the most severe form of heat-related illnesses, characterized by body temperature >40ºC and central nervous system dysfunction. Heatstroke is classified into Non-Exertional Heatstroke (NEHS) and Exertional Heatstroke (EHS). The pathophysiology of heatstroke involves a combination of direct heat effects on the host, the systemic inflammatory and coagulopathic response. The diagnosis of heatstroke based on Bouchama’s definition or Japan Association of Acute Medicine (JAAM) criteria. The basic principle of heatstroke management is early resuscitation and immediate cooling. Cold water immersion or convection evaporation method can be implemented based on the specific patient characteristic. Preventive strategies are early recognition by health workers, socialization to vulnerable groups and adequate acclimatization.